A inserção da educação ambiental na formação de professores: das percepções, às práticas - Wollmann, Ediane Machado (2016)
This research is about the Environmental Education in the teachers professional development, inserting itself in such initial, as in the permanent training of these professionals, since, this dimension is recommended to be applied in all the levels and teaching methods. To do it, it was developed training courses, where it was used different methodological strategies, like: theme workshops, Questioning methodology, among others. Besides, it sought to work with interdisciplinary aspects, multidisciplinary, conceptions and paradigms of Environmental Education in these teachers training. This research has a qualitative aspect and the data were analyzed by a Content Analysis, proposed by Bardin (2011). The first part of this research was developed in a Public School from Santa Maria RS. The second part was developed with Academic Chemistry Degree Course from Instituto Federal de Educação, Ciência e Tecnologia Farroupilha Campus Alegrete RS. With this study results it was created two scientific articles about a permanent training at school and a manuscript about the initial training. The first article detected the Environmental Education perception and the teachers environment participants, doing a relation with the teaching practices. The second article, consequently, talks about the description of a training Course accomplished with the school teachers that searched to help them in the Environmental Education insertion in their classes by their planning. The Manuscript 1, shows a description and thematic projects ally to the Integrated Professional Practice in the Chemistry Degree Course. The results showed how the perceptions can be and are related to the teaching practice, as well as how it is possible to insert in a meaningful way the Environmental Education in different level and teaching modality. We stress, therefore, the importance of this work, and it proposed to address a guiding principle critically considering the historical, political and social aspects, in addition to integrating the area of Science Education with other areas in order to improve teaching and learning.